2002
DOI: 10.1038/415436a
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of central nervous system embryonal tumour outcome based on gene expression

Abstract: Embryonal tumours of the central nervous system (CNS) represent a heterogeneous group of tumours about which little is known biologically, and whose diagnosis, on the basis of morphologic appearance alone, is controversial. Medulloblastomas, for example, are the most common malignant brain tumour of childhood, but their pathogenesis is unknown, their relationship to other embryonal CNS tumours is debated, and patients' response to therapy is difficult to predict. We approached these problems by developing a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,187
1
27

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 2,125 publications
(1,253 citation statements)
references
References 17 publications
38
1,187
1
27
Order By: Relevance
“…Tumors with identical histology and presumed state of differentiation might have very different growth characteristics and prognosis, and they apparently arise from different developmental lineages (Pomeroy et al, 2002). This is in agreement with the conclusion that cancer is a primarily a genetic disease.…”
Section: Cellular Origin Of Medulloblastomas and Astrocytomassupporting
confidence: 83%
See 1 more Smart Citation
“…Tumors with identical histology and presumed state of differentiation might have very different growth characteristics and prognosis, and they apparently arise from different developmental lineages (Pomeroy et al, 2002). This is in agreement with the conclusion that cancer is a primarily a genetic disease.…”
Section: Cellular Origin Of Medulloblastomas and Astrocytomassupporting
confidence: 83%
“…Moreover, a small percentage of sporadic medulloblastomas have mutations of Smoothened (SMO), a transmembrane protein that interacts with PTCH and is derepressed when Shh binds to PTCH (Dong et al, 2000;Zurawel et al, 2000;Taylor et al, 2002). Both familial and sporadic medulloblastomas with mutations of molecules in the Shh/PTCH pathway are typically of the desmoplastic histological variant (Hynes et al, 1995;Pietsch et al, 1997;Pomeroy et al, 2002).…”
Section: Developmental Mechanisms Promote the Growth Of Medulloblastomentioning
confidence: 99%
“…DNA microarray gene expression analyzed in tumor tissue from a large cohort of medulloblastoma patients showed that clinical outcome is predicted by the profile of gene expression, and is a better predictor than the expression or amplification of any single gene or any single gene mutation. 22 The results of the gene expression patterns and other genetic alterations are now being validated in the current Childrens Oncology Group (COG) protocols for medulloblastoma, and may complement clinical and histologic criteria for risk-stratification in future studies.…”
Section: Diagnostic/prognostic Modalitiesmentioning
confidence: 99%
“…Recent significant advances made in identifying key molecular markers/gene expression patterns of theses tumors should help to resolve controversy about PNET classification and better stratify them for future therapy. 22 Medulloblastoma, (infratentorial or cerebellar PNET), accounts for 20-25 % of pediatric brain tumors, making it the most common intracranial tumor of childhood. 49 In children, the tumor typically arises from the cerebellar vermis in the roof of the fourth ventricle into which it grows, filling the cavity and causing obstructive hydrocephalus.…”
Section: Common Pediatric Brain Tumors and Therapy Advancesmentioning
confidence: 99%
See 1 more Smart Citation